2008
DOI: 10.1103/physrevlett.100.056105
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Nucleation Mechanisms of Carbon Nanotubes in Catalytic Chemical Vapor Deposition

Abstract: The nucleation of carbon caps on small nickel clusters is studied using a tight binding model coupled to grand canonical Monte Carlo simulations. It takes place in a well defined carbon chemical potential range, when a critical concentration of surface carbon atoms is reached. The solubility of carbon in the outermost Ni layers, that depends on the initial, crystalline or disordered, state of the catalyst and on the thermodynamic conditions, is therefore a key quantity to control the nucleation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
171
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(182 citation statements)
references
References 27 publications
11
171
0
Order By: Relevance
“…This was used to study these systems at 1000 or 1500 K and provides good statistics for a variety of SWNT chiralities and initial distributions of the Ni atoms. This TB Hamiltonian has been developed specifically for nickel-carbon systems [13], and has been successfully used by Amara et al [12] to study the formation of graphitic carbon structures on Ni surfaces and clusters. Their study showed that solubility of carbon atoms in nickel is limited, but that carbon atoms are also stable at subsurface sites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was used to study these systems at 1000 or 1500 K and provides good statistics for a variety of SWNT chiralities and initial distributions of the Ni atoms. This TB Hamiltonian has been developed specifically for nickel-carbon systems [13], and has been successfully used by Amara et al [12] to study the formation of graphitic carbon structures on Ni surfaces and clusters. Their study showed that solubility of carbon atoms in nickel is limited, but that carbon atoms are also stable at subsurface sites.…”
Section: Methodsmentioning
confidence: 99%
“…Previous calculations include density functional theory (DFT) geometry optimisation [5,6], molecular dynamics [7,8], direct dynamics based on tight binding [9] and DFT [10,11] forces, and tight binding Monte Carlo (TBMC) simulations [12][13][14]. For example, previous TBMC simulations at 1000 K showed that Ni atoms that are uniformly distributed over an SWNT wall aggregate and diffuse to the open end of the SWNT, where they remain for the remainder of the simulation [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of C 2 fragments to a pre-formed cap with defined chirality was investigated by Gómez-Gualdrón et al [117]. Using a grand canonical MC simulation, Amara et al [118] investigated the nucleation of carbon caps on small nickel nanoparticles. A tip growth mechanism was demonstrated by Charlier et al [119].…”
Section: Detailed Atomistic Simulations Of Nanostructure Growth Procementioning
confidence: 99%
“…The simulations revealed that the inner walls of the bamboo structure start to nucleate at the junction between the outer nanotube wall and the catalyst particle. Amara et al [29] studied the nucleation of carbon caps on small nickel clusters using a tight-binding model coupled to grand canonical Monte Carlo simulations and found that an optimal chemical potential window exists for the carbon atom, to nucleate nanotube caps whose curvature matches with the local curvature of the catalyst particles. The solubility of carbon atoms in the outermost Ni layers depends on the initial state of the catalyst (crystalline or disordered) and on the thermodynamic conditions.…”
Section: Discrete Computational Modelingmentioning
confidence: 99%